2012
DOI: 10.1111/j.1553-2712.2012.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Patients With Longer Emergency Department Wait Times Less Likely to Consent to Research?

Abstract: Objectives: There are unique challenges to enrolling patients in emergency department (ED) clinical research studies, including the time-sensitive nature of emergency conditions, the acute care environment, and the lack of an established relationship with patients. Prolonged ED wait times have been associated with a variety of adverse effects on patient care. The objective of this study was to assess the effect of ED wait times on patient participation in ED clinical research. The hypothesis was that increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The raw value of WT is a quality indicator and may be associated with financial incentive, but the accuracy of recording and the collection method has never been evaluated. In France, EDs often use electronic support software for administrative tasks and WT analysis [5,6,9]. Locker and Mason [9] have previously reported that the recording of WT or ED length of stay could be unreliable, and may have been manipulated to follow targets such as the '4-h' in EDs from the UK.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The raw value of WT is a quality indicator and may be associated with financial incentive, but the accuracy of recording and the collection method has never been evaluated. In France, EDs often use electronic support software for administrative tasks and WT analysis [5,6,9]. Locker and Mason [9] have previously reported that the recording of WT or ED length of stay could be unreliable, and may have been manipulated to follow targets such as the '4-h' in EDs from the UK.…”
Section: Discussionmentioning
confidence: 98%
“…Whether this measure is reliable has never been studied, and a strong agreement between electronic record of waiting time (ERWT) and the true WT is mandatory to extrapolate the conclusions of clinical and administrative studies on this matter. Electronically recorded time is the reported variable described in recent studies or report that estimate WT or length of stay in the ED [5][6][7].…”
Section: Importancementioning
confidence: 99%